Machines and machinists: Capital-Skill Complementarity from an International Trade Perspective - Miklós Koren; Márton Csillag (Hungarian Academy of Sciences, Institute of Economics, 2011)
We estimate the effect of imported machines on the wages of machine operators utilizing Hungarian linked employer-employee data. We infer exposure to imported machines from detailed trade statistics of the firm and the occupation description of the worker. We find that workers exposed to imported machines earn about 8 percent higher wages than other machine operators at the same firm. When we proxy for unobserved worker characteristics, we find a significant 3 percent wage premium, suggesting that the relationship is causal. The return to schooling is also higher on imported machines. We build a simple matching model consistent with these findings. Our findings suggest that machine imports can be an important channel through which skill-biased technical change reaches less developed and emerging economies.
Keywords: F16; 330; imported machinery; capital-skill complementarity; wages; Arbeitskräfte; Arbeitsplatz; Fachkräfte; Maschine; Import; Lohnniveau; Ungarn